Heavy Metals Biosorption by Copper Resistant Bacteria of Acinetobacter sp. IrC2 - WAHYU IRAWATI; ADOLF JN PARHUSIP; NIDA SOPIAH (Microbiology Indonesia, 2015)
Â Heavy metal pollution is a serious problem because it cannot be degraded by natural processes and persist in soil, water, and sediment. Many indigenous microorganisms isolated from heavy metal contaminated sites had tolerance to heavy metals toxicity and could be used for bioremediation agent because of its capability to biosorb heavy metals. The aim of this research was to study the potency of copper resistant bacteria Acinetobacter sp. IrC2 as a biosorbent of heavy metals. Biosorption was determined by measuring the heavy metals concentration on growing medium by using atomic absorption spectrophotometer. The research showed that Acinetobacter sp. IrC2 was capable of growing in medium containing each of 2 mM of copper, zinc, lead, cadmium, and the mixture of those heavy metals. The addition of copper and lead in the medium changed morphological appearance of colonies to green and brown, respectively, suggesting that the survival mechanism of the isolate was by biosorbing copper or lead inside the cells. The percentage of heavy metals biosorption efficiency using live cells of Acinetobacter sp.IrC2 were up to 64.31% of copper, 24.73% of zinc, 62.79% of lead, and 11.56% of cadmium. Acinetobacter sp. IrC2 also reduced copper, lead, and cadmium concentration up to 24.30, 75.93, and 16.38%, respectively, in medium supplemented with 1 mM of the mixture of these heavy metals. The findings of this study indicated that Acinetobacter sp. IrC2 was a promising bacterium for removal of heavy metals.